(untitled) (African Journal of Biomedical Research, 2020)
Hearing disorders are common birth defect affecting about 1 to 3 out of every 1000 child births. Hearing represent a critical aspect of the social, educational, economical and cognitive development of the child. This paper studied the hearing threshold, pattern and prevalence of hearing impairment in primary school pupil in Ibadan North local Government area of Oyo state (IBNLGA). This cross-sectional study was carried out in IBNLGA. Two hundred and six primary school pupils were recruited for this study from January 10, 2016 to June 10, 2016. Informed consent was obtained from each pupil’s parent and thereafter, otoscopy and Pure tone audiometry (PTA) screening was carried out at the various schools. The data of each child screened was entered into the forms provided (Appendix i and ii) by the research assistants and crosschecked by the researcher. Data was analysed using Statistical Package for Social Science (SPSS) version 20. The percentage of male pupils that participated in the study was 52.9 while that of the female was 47.1. The mean age and ranged observed was 7.7 ± 1.6 years and 4 to 10years respectively. The pupils ages were evenly distributed with 94 pupils (45.7%) were between 4-7 years and 112 pupils (54.3%) were > 7years.The prevalence of hearing impairment in primary school pupils in IBNLGA was found to be 30.1% with females having a higher prevalence of 33.0% and males a lower prevalence of 27.2% respectively. This gender difference was however not statistically significant (X2,0.730, p=0.320). Of the 62 pupils with hearing impairment (hearing loss), 34 (54.8%) had Conductive Hearing Loss (CHL), 22(35.5%) had Sensorineural Hearing loss (SHL) and 6 (9.7%) had Mixed Hearing Loss (MHL). Furthermore, of the 62 pupils with hearing impairment, 29(46.8%) had moderate, 21 (33.8%) had mild, 12 (19.4%) had severe hearing impairment. None of the pupil exhibited slight and profound hearing impairment. The prevalence of hearing impairment in primary school pupils aged between 4-10 in Ibadan North Local Government Area was found to be 30.1%. Conductive hearing loss (CHL) was the most prevalent type of hearing impairment noted seen and in terms of severity, Moderate hearing loss accounted for major percentage of impairment observed